Influence of design implant and apical depth in post-extraction sockets: an in vitro simulated study - Marcelo Sales Cavalcante; Marcelo Ferraro-Bezerra; Paulo Goberlanio de Barros Silva; Gabriel Silva Andrade; Phillipe Nogueira Barbosa Alencar; Josfran da Silva Ferreira Filho; Lucas Alexandre Maia; Raul Anderson Domingues Alves da Silva; Danna Mota Moreira; Rafael Linard Avelar (BMC, 2023)
Abstract Background Implant design and apical stability are principal parameters involved in achieving successful primary stability. Using polyurethane models to simulate post-extraction sockets, we investigated the effects of using differing blade designs on the primary stability of tapered implants and the impact of apical depth. Method Six polyurethane blocks were used to simulate post-extraction pockets. One of the implants presented self-tapping blades (Group A), while the other (Group B) did not. Seventy-two implants were placed at 3 different depths (5 mm, 7 mm, and 9 mm), and a torque wrench was used to measure the stability of the implants. Results When evaluating the implants (placed at 5 mm, 7 mm, and 9 mm apical to the socket), we observed that the torque of the Group B implants was higher than that of Group A implants (P < 0.01). At the 9-mm depth, there was no difference between the groups (Drive GM 34.92 Ncm and Helix GM 32.33 Ncm) (P > 0.001), and considering the same implant groups, those placed at 7-mm and 9-mm depths presented higher torques (p < 0.01) than those placed at 5-mm (p > 0.01). Conclusion Considering both groups, we concluded that an insertion depth of greater than 7 mm is needed for initial stability, and in situations involving reduced supportive bone tissue or low bone density, a non-self-tapping thread design improves implant stability.